Webgis-Based Flood Disaster Inventory System in Karawang Regency - Yogi Hambali; Aji Primajaya; Adhi Rizal (International Journal of Education, Information Technology, and Others, 2023)
One of the natural disasters that often occurs in Karawang Regency is flooding. This is caused by high rainfall and the topography of Karawang Regency which tends to be low so that some areas can be submerged. However, along with the rapid development of information technology and Geographic Information System (GIS) in Indonesia, information technology plays an important role in the process of disaster management. The available spatial information can be in the form of facts resulting from events, raw data taken from measurement results, or derived data obtained from conclusions drawn from these facts and data. Therefore, the purpose of this research is to develop a WebGIS-based Karawang District Flood Disaster Inventory System. In its development, the Waterfall Software Development Life Cycle (SDLC) method is used starting from the analysis, design, coding, to testing stages. The results of the system testing are then identified using BlackBox. With this disaster inventory system, it is hoped that the flood disaster management process in Karawang Regency can be carried out more effectively and efficiently.